Variabel'nost' serdecnogo ritma v ocenke funkcional'nogo sostojanija volejbolistov (po programme "Omega-S") - Iordanskaya, F. A.; Malkin, R. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The work is devoted to the justification of using the methodology for assessing heart rate variability using the Omega-S program in monitoring volleyball players` training activities. The work is based on the results of dynamic observations of 80 elitevolleyball players, 21-33 years old, masters of sports (36 men and 44 women). The conducted studies allowed assessing the functional state of athletes according to a five-point assessment system provided by the Omega-S program. Individual analysis of the test results identified athletes with a reduced level of functional status. In the dynamics of the annual training cycle, the positive dynamics of the formation of a high fitness level in the group of men were determined, and in the group of women, 30% of the surveyed maintained only a satisfactory level of functional fitness. The results of the survey, team and individual indicators obtained promptly during training activities and in the screening approach, promptly identified athletes who need urgent correction of the condition and the need for additional diagnostic approaches. The conducted studies allowed to recommend the program "Omega-S" to the practice of volleyball at training events for the operational control of the tolerance of training loads.